Intelligence quotient analysis and its association with academic performance of medical students - Yesikar, Veena; Guleri, Sunil Kant; Dixit, Sanjay; Rokade, Rahul; Parmar, Sachin (International Journal Of Community Medicine And Public Health, 2017)
Background: Intelligence is the ability to see meaningful relationships between things that includes perceiving, knowing, reasoning and remembering. The study was done to know the duration of preparation, self study hours, academic performance and its association with IQ level of medical students, to state how to shorten the duration of completing MBBS degree. Methods: A cross sectional study done on 300 medical students using structured questionnaire derived from I Q test.com. Data collection and appropriate statistical test were applied considering p value ≤ 0.05 as significant. Results: Most of the medical students had near average intelligence (88.3%) , they undergone one to two years preparation for medical entrance exams and devoted much time (>6 hrs) in studies. 10% of the students had higher IQ, spare less time in their self study but were sincere in the classes. Conclusion: Students with near average IQ work hard in their studies and their academic performance was similar to students with higher IQ. So IQ can`t be made the basis for medical entrance; instead giving weight-age to secondary school results and limiting the number of attempts may shorten the time duration for entry and completion of MBBS degree.